2021
DOI: 10.1021/acsomega.0c05384
|View full text |Cite|
|
Sign up to set email alerts
|

Metastable Nanobubbles

Abstract: Water containing suspended nanobubbles is utilized in various applications. The observed lifetime of suspended nanobubbles is several weeks, whereas, according to the classical theory of bubble stability, a nanosized bubble should dissolve within microseconds. Explanations for the longevity of nanosized bubbles have been proposed but none of them has gained general acceptance. In this study, we derive an explanation for the existence of metastable nanobubbles solely from the thermodynamic principles. According… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 44 publications
1
13
0
Order By: Relevance
“…Physically, one would expect a concomitant increase in internal pressure to occur, and hence an outward force acting to restore the radius to its metastable value, reducing the likelihood of sub 10 nm bubbles. The existence of these barriers support the conclusions of the recent publication by Vehmas and Makkonen (2021) , which suggests that bubble dissolution becomes unlikely at small radii as the internal pressures increase significantly.…”
Section: Discussionsupporting
confidence: 86%
“…Physically, one would expect a concomitant increase in internal pressure to occur, and hence an outward force acting to restore the radius to its metastable value, reducing the likelihood of sub 10 nm bubbles. The existence of these barriers support the conclusions of the recent publication by Vehmas and Makkonen (2021) , which suggests that bubble dissolution becomes unlikely at small radii as the internal pressures increase significantly.…”
Section: Discussionsupporting
confidence: 86%
“…Under these conditions, we studied light scattering and absorbance during the chemical reaction. [26][27][28][29][30] Thus, initially we performed a combined study of dynamic light scattering and chemical reaction kinetics. As outlined in Figure SI3, we used a multi-timescale perspective, where individual light scattering count rate traces, measured consecutively during the chemical reaction, were used to construct time-correlation functions in the nanosecond to millisecond timescale, followed by evaluation of timedependent time-correlation functions as the chemical reaction proceeds.…”
Section: Time-dependent Dynamic Light Scatteringmentioning
confidence: 99%
“…We also note that the correlation function decay constants are associated with the hydrodynamic radius of the corresponding Brownian particle, which in the present case is an oxygen nanobubble. [26][27][28][29][30] From the data shown in Figures 2-4, we can thus further connect the equilibrium-averaged correlation times and count rates to nanobubble size and concentration, respectively. The dynamic light scattering measurements at the range of concentrations indicated in Table 1 showed that, under appropriate experimental conditions (initial reactant concentrations, overall reaction time, and colloidal system size) as shown here, it is possible to monitor oxygen nanobubble product formation by way of scattering.…”
Section: Time-dependent Dynamic Light Scatteringmentioning
confidence: 99%
“…For the same reason, ''an arbitrary constant pressure difference, independent of R'', used by Manning 1 in the derivation of the stability condition, is an inappropriate concept. The pressure difference cannot be arbitrary, because it is set by eqn (11) exactly at all times.…”
mentioning
confidence: 99%
“…The bubble stability problem must be solved by considering the thermodynamics of a complete liquid, gas, vapour system while properly treating the free energy of the interface, and considering the energy barriers that may lead to metastable nanobubbles. 11…”
mentioning
confidence: 99%